58.7k views
5 votes
Solve using the principles together . Don't forget to check. 5/6 y - 1/6 = 11/3 the solution is y =

1 Answer

4 votes

Solution:

Consider the following equation:


(5)/(6)y-(1)/(6)=(11)/(3)

solving for 5/6y, this is equivalent to:


(5)/(6)y=(11)/(3)+(1)/(6)=\text{ }(23)/(6)

that is:


(5)/(6)y=\text{ }(23)/(6)

that is:


(5y)/(6)=\text{ }(23)/(6)

by cross-multiplication, this is equivalent to:


5y=23

solving for y, we get:


y\text{ = }(23)/(5)

so that, we can conclude that the correct answer is :


y\text{ = }(23)/(5)

User Rsbarro
by
4.6k points